2015
DOI: 10.5811/westjem.2015.3.25284
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric and Medical Management of Marijuana Intoxication in the Emergency Department

Abstract: We use a case report to describe the acute psychiatric and medical management of marijuana intoxication in the emergency setting. A 34-year-old woman presented with erratic, disruptive behavior and psychotic symptoms after recreational ingestion of edible cannabis. She was also found to have mild hypokalemia and QT interval prolongation. Psychiatric management of cannabis psychosis involves symptomatic treatment and maintenance of safety during detoxification. Acute medical complications of marijuana use are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…Literature regarding such cases of “cannabis-induced psychosis” is limited, but the condition is believed to be the result of overconsumption of Δ 9 -THC, and many of the reported cases occur following ingestion of an edible (Bui, Simpson, & Nordstrom, 2015; Favrat et al, 2005; Hudak, Severn, & Nordstrom, 2015). …”
Section: Challenges Of Ediblesmentioning
confidence: 99%
“…Literature regarding such cases of “cannabis-induced psychosis” is limited, but the condition is believed to be the result of overconsumption of Δ 9 -THC, and many of the reported cases occur following ingestion of an edible (Bui, Simpson, & Nordstrom, 2015; Favrat et al, 2005; Hudak, Severn, & Nordstrom, 2015). …”
Section: Challenges Of Ediblesmentioning
confidence: 99%
“…Symptoms were reported to resolve within 6-12 h in about half of patients, but the literature is replete with reports that symptoms produced by both edibles and SCs can persist for significantly longer, lasting from days to several weeks in some patients (Hermanns-Clausen et al 2013;Hudak et al 2015;Bui et al 2015;Winstock et al 2015).…”
Section: Scope Of the Problemmentioning
confidence: 99%
“…However, there is a concern that the ongoing development of new strains of C. sativa containing increasingly higher levels of THC [6] may undermine its therapeutic potential and exacerbate adverse effects, including the potential for increased seizures [7,8] and psychosis [9]. In regard to the later effect, two recent cohort studies demonstrated that recreational cannabis use significantly increased incidence of psychosis [10] and was associated with a younger age of presentation [11], while acute THC poisoning following ingestion of high amounts of cannabis edibles was followed by an onset of severe psychosis in a recent case report on a 34-year-old Colorado woman [12]. …”
Section: Historical Perspective Of Medicinal Marijuanamentioning
confidence: 99%